2021
DOI: 10.2174/1573411017666210331113712
|View full text |Cite
|
Sign up to set email alerts
|

Ionic Liquids in Analytical Chemistry: Applications and Recent Trends

Abstract: Background: Ionic liquids (ILs) are a unique class of compounds consisting exclusively of cations and anions that possess distinctive properties such as low volatility, high thermal stability, miscibility with water and organic solvents, electrolytic conductivity and non-flammability. Ionic liquids have been defined as "design solvents", because it is possible to modify their physical and chemical properties by appropriately choosing cations and anions, in order to meet the specific characteristics based on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…The hydrogen storage methods can be classified as compressed gas storage, cryogenic hydrogen storage, cryo-compressed hydrogen such as the density, viscosity, and surface tension, can be changed by adjusting the cation and anion constituents. Therefore, one of the famous features of the ionic liquid is its 'designability' as there are a huge number of ion combinations and the possibility of designing the target-pointing ionic liquid [38].…”
Section: Introductionmentioning
confidence: 99%
“…The hydrogen storage methods can be classified as compressed gas storage, cryogenic hydrogen storage, cryo-compressed hydrogen such as the density, viscosity, and surface tension, can be changed by adjusting the cation and anion constituents. Therefore, one of the famous features of the ionic liquid is its 'designability' as there are a huge number of ion combinations and the possibility of designing the target-pointing ionic liquid [38].…”
Section: Introductionmentioning
confidence: 99%
“…[31] In 1959, Barber et al first reported the use of ILs as gas chromatographic stationary phases, [32] Since then, ILs-based gas chromatography stationary phases have been greatly developed. [33] In the early work, poor efficiencies, degraded analytes and poor peak shapes were obtained due to the fact that the molten salts had a limited temperature range between the time when they melted and the moment they decomposed. [34] In spite of such limitations, Armstrong et al detailed study and found that ILs have a major advantage for GC, namely their dual nature.…”
Section: Introductionmentioning
confidence: 99%
“…OLL phenols are mainly extracted using conventional solvents. However, recently, a move toward green methodologies under the name of green solvents, including ionic liquids (ILs) and deep eutectic solvents (DESs) or low-transition temperature mixtures (LTTMs), has emerged [16][17][18]. These new solvents aim at maximizing extraction efficiency and reaching new purposes such as researcher safety, environmental protection, and the use of a simplified and cheaper extraction procedure [19].…”
Section: Introductionmentioning
confidence: 99%